Surgical Management for Transposed Ovarian Recurrence of Cervical Cancer: A Systematic Review with Our Experience - Michihide Maeda; Tsuyoshi Hisa; Hiroki Kurahashi; Harue Hayashida; Misooja Lee; Reisa Kakubari; Shinya Matsuzaki; Seiji Mabuchi; Shoji Kamiura (Current Oncology, 2022)
In early-stage cervical cancer, ovarian metastasis is relatively rare, and ovarian transposition is often performed during surgery. Although rare, the diagnosis and surgical approach for recurrence at transposed ovaries are challenging. This study focused on the diagnosis and surgical management of transposed ovarian recurrence in cervical cancer patients. A 45-year-old premenopausal woman underwent radical hysterectomy, bilateral salpingectomy, and pelvic lymphadenectomy following postoperative concurrent chemoradiotherapy for stage IB1 cervical cancer. During the initial surgery, the ovary was transposed to the paracolic gutter, and no postoperative complications were observed. Ovarian recurrence was diagnosed using positron emission tomography–computed tomography, and a laparoscopic bilateral oophorectomy was performed. A systematic review identified nine women with transposed ovarian recurrence with no other metastases of cervical cancer, and no studies have discussed the optimal surveillance of transposed ovaries. Of those (n = 9), four women had died of the disease within 2 years of the second surgery, and the prognosis of transposed ovarian cervical cancer seemed poor. Nevertheless, three women underwent laparoscopic oophorectomies, none of whom experienced recurrence after the second surgery. Few studies have examined the surgical management of transposed ovarian recurrence. The optimal surgical approach for transposed ovarian recurrence of cervical cancer requires further investigation.